Literary criticism : an introduction to theory and practice - Bressler, Charles E. ([Place of publication not identifed] : Pearson Education, Incorporated, 2011)
Presents the thirteen basic schools of twentieth-century literary theory and criticism in their historical and philosophical contexts. Unlike other introductions to literary criticism, this text explores the philosophical assumptions of each school of criticism and provides a clear methodology for writing essays according to each school's beliefs and tenets
Chapter1. Defining criticism, theory, and literature -- Chapter2. A historical survey of literary criticism -- Chapter3. Russian formalism and new criticism -- Chapter4. Reader-oriented criticism -- Chapter5. Modernity/ Postmodernism structuralism/Poststructuralism: deconstruction -- Chapter6. Psychoanalytic criticism -- Chapter7. Feminism -- Chapter8. Marxism -- Chapter9. Cultural poetics or new historicism -- Chapter10. Postcolonialism -- Chapter11. African-American criticism -- Chapter12. Queer theory: Gay and Lesbian Criticism Chapter13. Ecocriticism .
Includes index.
Keywords: CRITICISM